2011
DOI: 10.1063/1.3643218
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of serrated flow in a bulk metallic glass

Abstract: Under compression loading, bulk metallic glasses (BMGs) irreversibly deform through shear banding manifested as a serrated flow behavior. By using a statistical analysis together with a complementary dynamical analysis of the stress-time curves during serrated flow, we characterize the distinct spatiotemporal dynamical regimes and find that the plastic dynamic behavior of a Cu50Zr45Ti5 BMG changes from chaotic to self-organized critical behavior with increasing strain rate. This plastic dynamics transition wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 26 publications
4
46
1
1
Order By: Relevance
“…11 Moreover, direct observation of the elastic energy relaxation during serration is impossible. Since the amplitude of stress undulation during serration events initially appears to be irregularly and stochastically distributed across the variant strain conditions produced by different loading rates and temperatures, 13,17 mechanistic trends are identified in these distributions by applying dynamic and statistical analyses. Using these methods, a better understanding of the mechanism is achieved despite the characteristic lack of periodicity in intermittent serrated flow behaviour.…”
Section: Dynamics Transition At Low Temperaturementioning
confidence: 99%
“…11 Moreover, direct observation of the elastic energy relaxation during serration is impossible. Since the amplitude of stress undulation during serration events initially appears to be irregularly and stochastically distributed across the variant strain conditions produced by different loading rates and temperatures, 13,17 mechanistic trends are identified in these distributions by applying dynamic and statistical analyses. Using these methods, a better understanding of the mechanism is achieved despite the characteristic lack of periodicity in intermittent serrated flow behaviour.…”
Section: Dynamics Transition At Low Temperaturementioning
confidence: 99%
“…The rising time at different strain rates covers a large time range because of different amplitudes of serration events, and the relaxation time roughly keeps constant. It is reported that with increasing strain rates from 10 −5 s −1 to 10 −2 s −1 , the loading time is several times the relaxation time, i.e., the rising time is far longer than the decreasing time, and even the maximum loading time and the relaxation time decrease four orders [37]. In addition, to explore the plastic deformation mechanisms for amorphous alloys at different strain rates, the time series analysis is helpful when a scalar time series is suspected to be a projection from a higher-dimensional dynamics, and a positive exponent is taken to be a signature of the underlying chaotic dynamics [38].…”
Section: Resultsmentioning
confidence: 99%
“…where ∆σ and ∆ε are the elastic stress and strain in one serration event [28], as shown in Figure 1b. A normalization of the elastic energy density is applied to eliminate the statistical error, since the plastic strain causes a drift of the elastic energy density values [23].…”
Section: Resultsmentioning
confidence: 99%
“…If given a strain value, it is obtained a function value of elastic energy density by the fitting function f(ε). Figure 3b,d are frequency distribution histograms, which display the N(s) versus S, where N(s) is the number of S. The stress drop generates shear bands, following a fractal structure [29], characteristic of a power-law relation, which indicates that shear banding may self-organize to a critical state, i.e., the SOC behavior occurs [20,28]. From Figure 3b, it is obvious that the number of S reveals an increasing and then decreasing trends, which is similar to a normal distribution.…”
Section: Resultsmentioning
confidence: 99%